2007
DOI: 10.1103/physrevstab.10.062002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the high-fieldQdrop in a high-purity large-grain niobium cavity for different oxidation processes

Abstract: The most challenging issue for understanding the performance of superconducting radio-frequency (rf) cavities made of high-purity (residual resistivity ratio >200) niobium is due to a sharp degradation (''Q-drop'') of the cavity quality factor Q 0 B p as the peak surface magnetic field (B p) exceeds about 90 mT, in the absence of field emission. In addition, a low-temperature (100-140 C) in situ baking of the cavity was found to be beneficial in reducing the Q-drop. In this contribution, we present the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 16 publications
(27 reference statements)
11
49
0
Order By: Relevance
“…Reversing an increase in R res and keeping the benefit in R BCS should allow minimizing the total surface resistance. We believe the observed Q 0 increase may stem from the decrease of the residual resistance by a single HF rinse consistent with earlier literature reports [5]. This means that the increase in R res caused by mild baking is due to the changes in either the oxide or in the first 1.5-2 nm of niobium underneath it.…”
Section: A Evolution Of Residual and Bcs Resistancessupporting
confidence: 91%
See 2 more Smart Citations
“…Reversing an increase in R res and keeping the benefit in R BCS should allow minimizing the total surface resistance. We believe the observed Q 0 increase may stem from the decrease of the residual resistance by a single HF rinse consistent with earlier literature reports [5]. This means that the increase in R res caused by mild baking is due to the changes in either the oxide or in the first 1.5-2 nm of niobium underneath it.…”
Section: A Evolution Of Residual and Bcs Resistancessupporting
confidence: 91%
“…It was reported that a single HF rinse applied on mild baked cavities does not bring the HFQS back [26] but there is no data in the literature for multiple HF rinse cycles. Anodizing experiments [4,5] showed that when about 20-30 nm of niobium are converted to oxide the HFQS reappears. This thickness corresponds to about 10-15 HF rinses in our experiments.…”
Section: High Field Q Slopementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a 120 C bake in UHV for 48 hours is known to often eliminate or mitigate high field rf losses, by pushing the onset of the HFQS to a higher peak surface magnetic field [6], and also to increase the residual component and decrease the BCS component of the rf surface resistance. The effect of the 120 C bake on a high field Q slope is also known to be confined to the first tens of nm from the surface, and in the first $hundred for BCS surface resistance [7][8][9], so a procedure like BCP completely reverses the benefit of the bake. By repeating the SR measurements before and after such treatments for the same samples, we measure the relative change in magnetic field penetration and magnetic volume fraction due exclusively to the effect of surface treatments and free from any geometrical effect.…”
Section: Introductionmentioning
confidence: 99%
“…The value of the energy gap obtained from fits of R s (T) at low RF field with BCS theory numerical calculations clearly showed a correlation between high gap values and high maximum B p -values [122]. Surface treatments such as BCP, EP, anodization, LTB do affect ∆ and therefore the ultimate field in the cavity.…”
Section: Surface Interstitials and Oxidementioning
confidence: 99%